Evaluation of a Computer-Guided Curriculum Using Animation, Visual Images, and Voice Cues to Train Patients for Peritoneal Dialysis. Issue 1 (January 2014) - Bernardini, Judith; Davis, Diane J.
Background: Training patients to perform peritoneal dialysis (PD) at home is key to good patient outcomes. Currently, no validated curriculum based on education concepts is available in the public domain, and training is not standardized. Few nurses are prepared to be effective trainers. The present study was designed to evaluate the efficiency and effectiveness of PD training using a new cycler designed with animation, visual images, and voice cues and provided by a qualified PD nurse with a standardized script to guide the trainer. Methods: The study recruited 40 participants, including individuals naive to dialysis and current automated PD (APD) patients. Participants with visual, hearing, or touch impairments were purposely included to reflect the disabilities common to the general APD population. The participants encompassed a range of self-reported computer and technical experience and education levels. Experienced training nurses trained each participant, one on one, for 4 – 8 hours during a single day; the nurses followed the standardized script as the participants progressed through the cycler training curriculum. The pace of training was adjusted to meet individual abilities and needs. Participants were evaluated by the training nurse at the end of the training session for their proficiency in meeting the learning objectives. Results: All 40 participants completed the 1-day training and successfully met all task objectives by the end of the day. Participant ages ranged from 23 to 73 years (mean: 53.8 ± 11 years), with the women (50 ± 12 years) being significantly younger than the men (57 ± 9 years, p = 0.05). Among the participants, 90% had visual impairments; 40%, hearing impairments; and 45%, touch impairments. Twenty-nine participants (73%) had multiple impairments. Median training time was 7 ± 0.13 hours, with a range of 5 – 8.25 hours. We found no correlation between the number of hours needed for successful training and age ( r = 0.30). Training time did not differ significantly by sex, disability, computer or technical experience, or education level. The required training time was less for participants with previous PD experience (6.5 ± 0.7 hours) than for those naive to dialysis (7 ± 0.8 h), but at p = 0.056, the difference just missed being statistically significant. Conclusions: The most striking finding is that, despite a variety of barriers to learning, all 40 participants were able to meet all the stated objectives of the study with 4 – 8 hours of training. Ability to meet the study objectives was not less for participants with limited education or limited technical or computer experience than for those with more education or more advanced technical and computer skills. Thus, the highly technical aspect of the new cycler is able to promote learning for a wide range of learners. The cycler provides automated instruction using audio, video, and animation, and those features, combined with a qualified training nurse using a standardized script, appear to be both efficient and effective.